3 Implementing a safer obstetric handover. (31st October 2017) - Patel, Kayur; Lee, Sindy; Holroyd, Charlotte
Abstract : Background: Handover is an important part of continuity of safe care for patients. Obstetric anaesthesia is a high-risk area in which handover and follow up of patients is important. In our anaesthetic department, no formal handover process existed for this group of patients. Method: We looked to introduce a well-established 'SAFER' (Sick patients, At risk patients, Follow ups, Epidurals, and Remote patients) handover tool in our department. This was supported by all trainees who felt there should be a more formalised process as 80% had received an inadequate handover at some point. Alongside the SAFER tool we added a table that mimicked the layout of labour ward so notes could be made alongside room names. By making the document user friendly we felt it would lead to better compliance and sustainability. Result: Using a PDSA (Plan-Do-Study-Act) methodology we introduced our intervention which initially led to a 63% compliance. We listened to trainee and consultant feedback, made changes to the handover document, changed the nature of the handover process and now compliance is 83%. In order to plot progress, we used a run chart with multiple cycles. Conclusion: We have introduced a low-cost solution to providing a documented handover process which has improved safety where originally nothing existed. We are working with all trainees to reach 100% compliance.